1988
DOI: 10.1128/jb.170.10.4960-4962.1988
|View full text |Cite
|
Sign up to set email alerts
|

Fine structures of the capsules of Klebsiella pneumoniae and Escherichia coli K1

Abstract: The fine structures of the capsules of Klebsiella pneumoniae and Escherichia coli were determined by the rapid-freezing technique. The capsular layer was seen as a densely packed accumulation of fine fibers. The thickness of the capsule was approximately 160 nm in K. pneumoniae and less than 10 nm in E. coli Kl. Two layers were observed in the Klebsiella capsule in which the arrangements of the fibers were different. The inner layer of the capsule was formed by a palisade of thick and dense bundles of the fibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
34
0
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 17 publications
4
34
0
1
Order By: Relevance
“…For P. antarctica cells, the presence of an inner layer of oriented packed fibres extending perpendicularly away from the cell envelope, as well as an outer layer of randomly distributed fine fibres could be regarded as a capsule. These two polymeric arrangements have also been reported for capsules from Escherichia coli K1 and Klebsiella pneumoniae K (Amako et al ., 1988). Other encapsulated bacteria have been observed by TEM following HPF‐FS (Graham et al ., 1991; Korenevsky et al ., 2002).…”
Section: Discussionsupporting
confidence: 69%
“…For P. antarctica cells, the presence of an inner layer of oriented packed fibres extending perpendicularly away from the cell envelope, as well as an outer layer of randomly distributed fine fibres could be regarded as a capsule. These two polymeric arrangements have also been reported for capsules from Escherichia coli K1 and Klebsiella pneumoniae K (Amako et al ., 1988). Other encapsulated bacteria have been observed by TEM following HPF‐FS (Graham et al ., 1991; Korenevsky et al ., 2002).…”
Section: Discussionsupporting
confidence: 69%
“…The surface of normal K. pneumo niae was covered with a very thick fibrous cap sular material layer (160 nm). The findings were similar to the capsular material of K. pneumoniae fixed by a rapid-freezing tech nique reported by Amako et al [12], by which the capsular material can be observed in its most natural state. After treatment with cefpimizole, which had the lowest bactericidal activity, the bacteria became filamentous, and the thickness of the capsular material layer was thinner (90 nm) than that of the normal bacte ria.…”
Section: Discussionsupporting
confidence: 76%
“…The complete capsule is about 10 nm thick. This thickness is notably less than that of other capsules: e.g., Klebsiella pneumoniae, with a similar layout, is about 160 nm thick (10). However when the E. coli Kl capsule was stabilized with antibodies, much higher values for the capsular thickness were obtained, i.e., >300 nm (115).…”
Section: Capsule Structurementioning
confidence: 87%
“…By this technique, the capsule of E. coli Ki has been observed to consist of two layers, an inner and an outer one (10). The fibrous material of the inner layer forms a dense stratum which is probably made up of a series of thick bundles set perpendicular to the outer membrane surface.…”
Section: Capsule Structurementioning
confidence: 99%